Pengaruh Suku Bunga, Pendapatan Perkapita, dan Inflasi Terhadap Investasi Dalam Negeri di Provinsi D.I Yogyakarta - Anastasia Susanti Mete; Atika Fatimah; Amelia Shahira Anadhianti (FEB Universitas Sultan Ageng Tirtayasa, 2023)
D.I Yogyakarta Province's domestic investment has fluctuated for the past six years. However, in 2020 there was a very drastic decrease of IDR 3.615,4 billion from 2019. This study aims to analyze the effect of interest rates, per capita income and inflation on domestic investment in the Province of D.I Yogyakarta. The analytical method used is multiple linear regression with time series data from 1992-2021. The results of the study show that interest rates have a significant positive effect on domestic investment in the Province of D.I Yogyakarta. Income per capita has no significant effect on domestic investment in the Province of D.I Yogyakarta because the low provincial minimum wage makes people more concerned with their living expenses. Inflation has a significant negative effect on domestic investment in the Province of D.I Yogyakarta because the increase in inflation in 2021 is caused by a decrease in people's purchasing power.